2010
DOI: 10.1007/s00449-010-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of steady-state phenol degradation in a pulsed plate bioreactor with immobilised cells of Nocardia hydrocarbonoxydans

Abstract: A novel bioreactor called pulsed plate bioreactor (PPBR) with cell immobilised glass particles in the interplate spaces was used for continuous aerobic biodegradation of phenol present in wastewater. A mathematical model consisting of mass balance equations and accounting for simultaneous external film mass transfer, internal diffusion and reaction is presented to describe the steady-state degradation of phenol by Nocardia hydrocarbonoxydans (Nch.) in this bioreactor. The growth of Nch. on phenol was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
9
0
4
Order By: Relevance
“…Nocardia hydrocarbonoxydans NCIM 2386 has been reported to effectively degrade phenol in batch and continuous flow systems, both as free cells and in immobilized form [7,8]. The pathway for phenol degradation by N. hydrocarbonoxydans NCIM 2386 has not been reported yet.…”
Section: Desalination and Water Treatmentmentioning
confidence: 93%
See 3 more Smart Citations
“…Nocardia hydrocarbonoxydans NCIM 2386 has been reported to effectively degrade phenol in batch and continuous flow systems, both as free cells and in immobilized form [7,8]. The pathway for phenol degradation by N. hydrocarbonoxydans NCIM 2386 has not been reported yet.…”
Section: Desalination and Water Treatmentmentioning
confidence: 93%
“…The trend of the plot shows substrate inhibition by phenol. Shetty et al [8] showed that the rate equation for growth of N. hydrocarbonoxydans followed Haldane model when ammonium nitrate was used as a nitrogen source and hence the rate of phenol degradation was also reported to follow the same model with the maximum growth rate (μ max ) for this microorganism for its growth on phenol being replaced with v max = μ max /Y x/s , where v max is the maximum rate of phenol degradation and Y x/s is the yield coefficient in mg biomass produced/mg phenol consumed. In the presently reported work, where peptone was used as a nitrogen source, Haldane model did not fit well though substrate inhibition was observed.…”
Section: Kinetics For Total Phenol Degradationmentioning
confidence: 98%
See 2 more Smart Citations
“…To sum up, the above two cases25, 35 reflected the difficulty and limitations of assuming biofilm homogeneity in BGAC modeling. Therefore, biofilm in most BGAC studies was assumed to be a homogeneous phase, even for those developed on other support materials other than GAC 33, 36…”
Section: Mathematical Description Of Biofilm Phase On Bgac Particlementioning
confidence: 99%